Case report and clinical databased research study on malaria - Naitik D Trivedi; Upama N Trivedi; Anil Bhandari; Madhubhai M Patel; Nishant Upadhyay (Wolters Kluwer Medknow Publications, 2010)
Malaria is endemic in Gujarat and the adjoining areas like many other parts of the India. Depending upon the environmental conditions different species of malarial parasite are found in different areas. The present study was planned to see the pattern of malarial infection diagnosed at B.J. Desai Trust Hospital, Kheda, Gujarat. Methods: Giemsa stained thick and thin blood films of indoor and outdoor febrile patients sent to the laboratory of B.J. Desai Trust Hospital, Kheda, Gujarat with a suspicion of malaria, were examined. Thick film was examined for the diagnosis of malaria while thin films were seen to know the species. Results: Out of 1994 patients screened, 145 (7.2%) were found infected. Plasmodium vivax was seen in the majority (72.47.2%). Plasmodium falciparum was the second common species detected in 24.1 % cases. Mixed infection was seen in 3.44% cases while Plasmodium malariae and ovale was not seen in any patient. Conclusion: Plasmodium vivax was the commonest type of malaria diagnosed at Kheda District in Gujarat, during 2008- 2009.